The response regulator RssB controls stability of the sigma(S) subunit of RNA polymerase in Escherichia coli. - Muffler, A (1996)
The rpoS-encoded sigma(S) subunit of RNA polymerase is a central regulator in a regulatory network that governs the expression of many stationary phase-induced and osmotically regulated genes in Escherichia coli. sigma(S) is itself induced under these conditions due to an increase in rpoS transcription (only in rich media) and rpoS translation as well as a stabilization of sigma(S) protein which in growing cells is subject to rapid turnover. We demonstrate here that a response regulator, RssB, plays a crucial role in the control of the cellular sigma(S) content. rssB null mutants exhibit nearly constitutively high levels of sigma(S) and are impaired in the post-transcriptional growth phase-related and osmotic regulation of sigma(S). Whereas rpoS translational control is not affected, sigma(S) is stable in rssB mutants, indicating that RssB is essential for sigma(S) turnover. RssB contains a unique C-terminal output domain and is the first known response regulator involved in the control of protein turnover.